K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

9 tháng 7 2018

\(a)\) \(\left(x-y\right)^3\left(y-z\right)^3\left(z-x\right)^3\)

\(=\)\(\left[\left(x-y\right)\left(y-z\right)\left(z-x\right)\right]^3\)

\(b)\) \(\left(a+b+c\right)^3-a^3-b^3-c^3\)

\(=\)\(a^3+b^3+c^3+3\left(a+b\right)\left(b+c\right)\left(c+a\right)-a^3-b^3-c^3\)

\(=\)\(3\left(a+b\right)\left(b+c\right)\left(c+a\right)\)

Chúc bạn học tốt ~ 

5 tháng 9 2018

\(a^3+b^3+c^3-3abc\)

\(=\left(a+b\right)^3-3ab\left(a+b\right)+c^3-3abc\)

\(=\left(a+b+c\right)\left[\left(a+b\right)^2-\left(a+b\right)c+c^2\right]-3ab\left(a+b+c\right)\)

\(=\left(a+b+c\right)\left(a^2+b^2+c^2-ab-bc-ca\right)\)

9 tháng 7 2018

a,\(x^2-2xy+2y^2+2y+1=\left(x^2-2xy+y^2\right)+\left(y^2+2y+1\right)=\left(x-y\right)^2+\left(y+1\right)^2\)

b,\(4x^2-4x+y^2+2y+2=\left(4x^2-4x+1\right)+\left(y^2+2y+1\right)=\left(2x-1\right)^2+\left(y+1\right)^2\)

c, \(z^2-6z+5-t^2-4t=\left(z^2-6z+9\right)-\left(t^2-4t+4\right)=\left(z-9\right)^2-\left(t-2\right)^2\)